Rapunzel Syndrome in a Postpartum Patient after Caesarian Delivery - Andrade, Darren J. (ACG Case Rep J, 2014)
A trichobezoar is an immobile, indigestible collection of hair or hair-like fibers that accumulates within the GI tract. Rapunzel syndrome is a rare variant in which a trichobezoar extends into the small intestine, potentially causing obstruction. We describe the first case, to our knowledge, of Rapunzel syndrome occurring in a postpartum patient after delivery by Caesarian section.